Review of the systematics of Trachagathis Viereck (Hymenoptera: Braconidae: Agathidinae) - Sharkey, Michael (Zootaxa, 2006)
The phylogenetic position of Trachagathis Viereck is discussed. Two new combinations are proposed. Agathis rubricincta Ashmead (1894) and Agathis depressifrons Braet and van Achterberg (2003) are transferred to Trachagathis, Trachagathis rubricincta n. comb. and T. depressifrons n. comb. Elasmopalpus lignosellus (Zeller) Pyralidae, the lesser cornstalk borer, is recorded as a host of T. rubricincta.